Red mud-based oxygen carrier as well as preparation method and application thereof

By using Bayer method red mud with high iron content and industrial solid waste or limestone with high calcium content, the problem of serious wear of the oxygen carrier during fluidization is solved, and the low energy of the oxygen carrier is achieved It consumes low cost and has high fluidized wear resistance, which meets the demand for multiple cycle oxygen carrying capacity of oxygen carriers during chemical chain combustion.

CN119462076APending Publication Date: 2025-02-18CHINA DATANG GRP TECH INNOVATION CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411687784.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing chemical chain combustion oxygen carriers have severe wear during fluidization, resulting in reduced particle size and loss of oxygen carriers, and high energy consumption and high cost in the preparation process.

Method used

Using Bayer red mud with high iron content and high calcium content industrial solid waste or limestone as raw materials, reduces preparation energy consumption through low-cost additives and granulation technology, and forms high-strength silicon-aluminum calcium through calcium additives and heat treatment. Microcrystalline glass improves fluidized wear resistance of oxygen carrier.

Benefits of technology

It realizes low energy consumption and low cost preparation of oxygen carrier, improves fluidized wear resistance of oxygen carrier, extends the circulation service life of oxygen carrier, and meets the multiple cycle loading of oxygen carrier during chemical chain combustion. oxygen capacity requirement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462076A_ABST
    Figure CN119462076A_ABST
Patent Text Reader

Abstract

The invention discloses a red-mud-based oxygen carrier and a preparation method and application thereof. The red mud-based oxygen carrier comprises the following raw materials: red mud powder and high-calcium additive powder, and the weight ratio of the red mud powder to the high-calcium additive powder is (3-4): (1-2). The preparation method of the red mud-based oxygen carrier comprises the following steps: 1) pretreating raw materials; (2) preparing a red mud-based oxygen carrier precursor; 3) granulation and high-temperature heat treatment; and 4) processing and obtaining of a red mud-based oxygen carrier finished product, the red mud-based oxygen carrier has the advantages of low cost, realization of waste reutilization, high fluidization wear resistance, reasonable preparation energy consumption and up-to-standard circulating oxygen carrying capability, and the red mud-based oxygen carrier has a wide industrial application market in the application scene of fluidization chemical looping combustion due to the advantages.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of chemical looping combustion and resource utilization of industrial solid waste. The present invention discloses a method for preparing a low-energy, low-cost, high-fluidization-strength oxygen carrier for chemical looping combustion and gasification using high-iron-content Bayer red mud and high-calcium-content industrial solid waste or limestone and other raw materials. Background Art

[0002] Chemical looping combustion technology is a combustion technology that efficiently separates carbon dioxide. During the chemical looping combustion process, the oxygen carrier is oxidized by oxygen in the air in the air reactor and then reduced by the carbon-containing fuel in the fuel reactor. Through the circulation of the oxygen carrier in the two reactors, the air and the combustion flue gas are separated into two different reactors. The carbon dioxide produced by the reaction of the oxygen carrier and the carbon-containing fuel in the fuel reactor will not be diluted by air, thereby maintaining a high concentration of more than 80%, which is conducive to the subsequent capture of carbon dioxide.

[0003] Oxygen carriers are the core of realizing the step-by-step oxidation and reduction processes in chemical chain combustion, and are also the bridge that connects the two processes. Oxygen carriers need to have strong redox activity, converting oxygen in the air into lattice oxygen in the solid in the air reactor, and releasing lattice oxygen in the fuel reactor to react with the fuel. At present, mainstream oxygen carriers can be divided into nickel-based, copper-based, cobalt-based, manganese-based, iron-based, sulfur-based oxygen carriers, etc. Considering the cost, oxygen carrying capacity, reactivity and stability of the oxygen carrier, the cost of iron-based oxygen carriers and industrial production are more cost-effective, and the preparation of oxygen carriers from minerals and solid wastes with high iron content further reduces the cost, such as iron ore, ilmenite, red mud, slag, steel slag, etc.

[0004] Red mud is a solid waste discharged during the industrial refining of alumina. In 2023, my country's red mud emissions exceeded 100 million tons. The process methods are mainly divided into sintering method and Bayer process. Among them, the Bayer process is currently dominant due to its low energy consumption, but it has higher requirements for the grade of bauxite raw materials. The high iron content itself causes the Bayer process red mud to contain a high level of iron oxide, which can be used to prepare low-cost chemical chaining combustion oxygen carriers. In the actual industrial application of chemical chaining combustion conditions, in addition to the indicators of fuel conversion rate and carbon dioxide selectivity, the wear rate of oxygen carrier particles after multiple cycles during fluidization needs to be maintained at a low level, and the wear resistance strength of fluidization should be improved on the basis of the original red mud-based oxygen carrier.

[0005] The wear strength of red mud raw materials is low, and it needs to be processed to meet the fluidization strength requirements of oxygen carriers in chemical looping combustion. In addition, if the particle size of red mud powder is too small, it will enter the fly ash and cause oxygen carrier loss. Sintering granulation can effectively improve the hardness, wear strength and particle size of red mud oxygen carriers. However, the sintering temperature of pure red mud is too high, the energy cost is huge, and the wear strength of the sintered body is limited.

[0006] Invention patent CN115072658A discloses a method for preparing a modified red mud oxygen carrier for methane chemical loop steam reforming, using Ni and Ce salt solutions added to water-washed neutral red mud, calcined in a muffle furnace at 950 degrees Celsius for 3 hours after ultrasonic treatment, and ground and sieved to obtain a modified red mud oxygen carrier of 150 to 300 microns. The reaction activity and cycle stability were tested in a fixed bed reactor, and the results were good. However, the cost of the modified additives Ni and Ce of the invention is relatively high, making it difficult to apply them on a large scale industrially; and the test using a fixed bed reactor cannot guarantee the strength of the oxygen carrier under actual fluidized conditions. Summary of the invention

[0007] The following is a summary of the subject matter described in detail herein. This summary is not intended to limit the scope of the claims.

[0008] In view of the economic problem of oxygen carriers in chemical looping combustion, red mud, a solid waste from the aluminum smelting industry with a high iron content, is selected as a low-cost and cost-effective oxygen carrier. The energy consumption of preparation is reduced by means of low-cost additives and granulation. In view of the problem that red mud-based oxygen carriers are excessively worn during the fluidized transport and reaction process of the chemical looping combustion double fluidized bed reactor, resulting in the loss of oxygen carriers due to the reduction of particle size, which leads to the escape into the flue gas, a red mud-based oxygen carrier that meets the particle size requirements of 150 to 350 microns and has high wear resistance is obtained through preparation methods. On this basis, it meets the requirements of chemical looping combustion for oxygen carrier oxygen carrying capacity and reaction activity.

[0009] By adding an appropriate amount of other minerals or industrial solid wastes with high calcium content, such as limestone, sintered red mud, steel slag, etc., into red mud, a low-temperature eutectic is formed with the high silicon and aluminum content in Bayer red mud. It can melt at a certain temperature and generate high-strength silicon-aluminum-calcium glass-ceramics, thereby preparing a red mud-based high-strength oxygen carrier that meets the fluidization requirements of chemical chain combustion with low energy consumption.

[0010] The first aspect of the present application provides a red mud-based oxygen carrier, wherein the raw materials of the red mud-based oxygen carrier include red mud powder and high calcium additive powder, wherein the weight ratio of the red mud powder to the high calcium additive powder is (3-4):(1-2); for example, 3:2, 3.5:1.5, 4:1 or any two of them as range values ​​between endpoint values, but are not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0011] In an exemplary embodiment, the raw materials of the red mud-based oxygen carrier are composed of red mud powder and high calcium additive powder, wherein the weight ratio of the red mud powder to the high calcium additive powder is (3-4): (1-2).

[0012] In an exemplary embodiment, the red mud powder and the high calcium additive powder are obtained by pre-treating the red mud raw material and the high calcium additive. The red mud raw material is usually derived from the solid waste discharged during the Bayer process of refining alumina using high-grade bauxite as raw material. The Bayer red mud raw material obtained by this method is usually discharged in the form of mud, and the original red mud accumulated in the dam after treatment has a high water content and is in the form of mud blocks.

[0013] In an exemplary embodiment, the pretreatment includes: drying, crushing, baking, and ball milling the red mud raw material and the high calcium additive to obtain the red mud powder and the high calcium additive powder.

[0014] In an exemplary embodiment, the red mud powder and the high calcium additive powder have a particle size of 5-50 microns.

[0015] In an exemplary embodiment, the red mud raw material has an iron oxide content of more than 40% by mass; and a sum of silicon dioxide and aluminum oxide contents of more than 30% by mass.

[0016] In an exemplary embodiment, the iron oxide content in the red mud raw material is 44.7% by mass.

[0017] In an exemplary embodiment, the high calcium additive is an ore or industrial solid waste with a high calcium content, such as any one of limestone, sintering red mud, high calcium steel slag, high calcium slag, and the like.

[0018] In an exemplary embodiment, the calcium oxide content in the high-calcium additive is greater than 40% by mass, for example, 50.4%, 55.3%, 46.7%, 43.7%, or 40.5%.

[0019] The second aspect of the present application provides a method for preparing the above-mentioned red mud-based oxygen carrier, comprising: 1) Pretreatment of raw materials; 2) Preparation of red mud-based oxygen carrier precursors; 3) Granulation and high temperature heat treatment; and 4) Processing and obtaining of red mud-based oxygen carrier finished products.

[0020] In an exemplary embodiment, step 1) includes: drying, crushing, drying, and ball milling the red mud raw material and the high calcium additive to obtain red mud powder and high calcium additive powder.

[0021] In an exemplary embodiment, in step 1), the drying is air-drying or sun-drying.

[0022] In an exemplary embodiment, in step 1), the drying comprises drying in an oven at a temperature of 100-120° C. for a drying time of 10-14 h; Preferably, the drying temperature is 105° C. and the drying time is 12 h.

[0023] In an exemplary embodiment, step 2) includes: mixing the red mud powder with the high calcium additive powder to form a red mud-based oxygen carrier precursor.

[0024] In an exemplary embodiment, in step 2), in the red mud-based oxygen carrier precursor, the mass fractions of calcium, magnesium, silicon and aluminum are all calculated in the form of oxides, and the sum of the mass fractions of calcium oxide and magnesium oxide is equal to the sum of the mass fractions of silicon dioxide and aluminum oxide.

[0025] In an exemplary embodiment, in step 2), the mixing includes: mechanically mixing the red mud powder and the high calcium additive powder, or mixing the red mud powder and the high calcium additive powder in the form of slurry.

[0026] In an exemplary embodiment, in step 2), when the red mud powder and the high calcium additive powder are mixed in the form of slurry, the pretreatment in step 1) may omit drying and ball milling.

[0027] Among them, the mechanical mixing is conducive to off-site use after transportation, while mixing in the form of slurry is conducive to on-site use.

[0028] In an exemplary embodiment, in step 2), the red mud-based oxygen carrier precursor needs to have a relatively high iron content, with the ferric oxide content being above 25% by mass, so the use of industrial solid waste containing iron and calcium is a more efficient and environmentally friendly option.

[0029] In an exemplary embodiment, step 3) includes: pressing and molding the red mud-based oxygen carrier precursor to obtain a brick-shaped body; and calcining the brick-shaped body at a high temperature to obtain an oxygen carrier sintered brick.

[0030] In an exemplary embodiment, in step 3), the pressing and molding comprises: placing the red mud-based oxygen carrier precursor into a mold, and pressing it into a brick-shaped body using a hydraulic press.

[0031] In an exemplary embodiment, the hydraulic press is a 2000 ton hydraulic press.

[0032] In an exemplary embodiment, in step 3), when the red mud-based oxygen carrier precursor is mixed in the form of a slurry, the pressing molding further includes: after pressing, the wet brick mold body of the red mud-based oxygen carrier precursor is first dried to control the moisture content to below 20%, for example, natural drying by air drying or artificial drying in an oven can be used.

[0033] In an exemplary embodiment, in step 3), the high-temperature calcination includes: placing the brick body into a kiln for sintering bricks for high-temperature calcination.

[0034] In an exemplary embodiment, the high temperature calcination temperature is 1200-1400°C, for example, 1200°C, 1300°C, 1400°C or any two of them as a range value between endpoint values, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0035] In an exemplary embodiment, the high temperature calcination temperature is 1200°C.

[0036] In an exemplary embodiment, the high-temperature calcination time is; preferably, the time is 5 hours.

[0037] In an exemplary embodiment, step 4) includes: cooling, crushing and screening the red mud-based oxygen carrier sintered bricks to obtain the red mud-based oxygen carrier finished product.

[0038] In an exemplary embodiment, in step 4), the red mud-based oxygen carrier is a particle with a particle size of 150 to 350 microns.

[0039] The third aspect of the present application provides a red mud-based oxygen carrier prepared by the above-mentioned method for preparing a red mud-based oxygen carrier.

[0040] The fourth aspect of the present application provides an application of the above-mentioned red mud-based oxygen carrier in a chemical looping combustion / gasification process.

[0041] Compared with the existing related technologies, this application mainly has the following technical advantages: (1) Low cost. The red mud-based oxygen carrier described in the present application is an iron-based oxygen carrier, which uses high-iron-content Bayer red mud and high-calcium ore or solid waste as raw materials. No high-cost catalysts or additives are added during the production and processing process, and the process does not involve rare or difficult processes. All production and processing processes are mature processes that can be applied on a large scale in industry, which is convenient for large-scale production to reduce costs.

[0042] (2) Realize waste recycling. This application realizes the high added value comprehensive utilization of high iron content Bayer red mud and high calcium iron industrial solid waste, such as sintering red mud, steel slag, blast furnace slag, etc. In addition to being able to be recycled and reused in the chemical chain combustion process, the red mud-based oxygen carrier reduced in the fuel reactor can be refined into reduced ferroferric oxide or iron element by magnetic separation.

[0043] (3) High wear resistance of fluidization. The present application obtains a red mud-based oxygen carrier with high wear resistance by sintering or melting, which can meet the high requirements for wear resistance of fluidized oxygen carriers in industrial applications using circulating fluidized beds.

[0044] (4) Reasonable energy consumption for preparation. The present application forms a calcium-aluminum-silicon low-temperature eutectic by adding an appropriate amount of calcium-containing ore or industrial solid waste to the high-iron-content Bayer red mud, thereby reducing the melting temperature of the heat treatment and the energy consumption of sintering or melting to prepare the high-strength oxygen carrier product.

[0045] (5) Cyclic oxygen carrying capacity meets the standard. The oxygen carrier prepared in this application contains more than 25% by mass of hematite, which meets the standard requirement of chemical looping combustion for the oxygen carrier to maintain oxygen carrying capacity after multiple cycles.

[0046] In summary, the red mud-based oxygen carrier has the advantages of low cost, waste recycling, high wear resistance of fluidization, reasonable energy consumption for preparation, and up-to-standard cyclic oxygen carrying capacity. These advantages make this application have a wide range of industrial application markets in the application scenarios of fluidized chemical chaining combustion. Red mud-based oxygen carrier particles that meet the requirements of chemical chaining combustion particle size and mild wear of fluidization are obtained through preparation means such as calcium additives and heat treatment. It has a service life of more than 30 cycles and fluidization for more than 12 hours without wear, which meets the requirements of oxygen carrying capacity of oxygen carriers in chemical chaining combustion. Through this application, a red mud-based high-strength chemical chaining combustion oxygen carrier can be obtained. This application is that it can reduce the cost of preparing raw materials, recycle industrial solid wastes such as red mud, enhance the wear resistance of oxygen carriers during fluidization, reduce energy consumption in the preparation process, and meet the demand for cyclic oxygen carrying capacity of oxygen carriers in chemical chaining combustion. The preparation process of red mud-based oxygen carriers can realize large-scale industrial production.

[0047] Other features and advantages of the present application will be described in the following description, and partly become apparent from the description, or be understood by implementing the present application. Other advantages of the present application can be realized and obtained by the schemes described in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] The accompanying drawings are used to provide an understanding of the technical solution of the present application and constitute a part of the specification. Together with the embodiments of the present application, they are used to explain the technical solution of the present application and do not constitute a limitation on the technical solution of the present application.

[0049] Figure 1 The X-ray diffraction (XRD) results of Bayer red mud in Liaocheng, Shandong; Figure 2 For Figure 1 XRD results of the products obtained by mixing the treated Bayer process red mud powder and limestone powder in mass ratios of (1) 10:0, (2) 9:1, (3) 8:2, (4) 7:3, and (5) 6:4 and then heat-treating them in a muffle furnace at 1200°C for 5 hours.

[0050] Figure 3 This is the test result of the cyclic oxygen carrying capacity of the product of red mud powder and limestone powder in a mass ratio of 6 to 4. DETAILED DESCRIPTION

[0051] The present invention is further described in detail below through specific embodiments and drawings. It should be understood that the described embodiments are only used to explain the present invention, but not to limit the present invention.

[0052] Unless otherwise specified, the materials and reagents used in the examples of the present invention can be obtained from commercial sources. Experimental methods without specific conditions in the examples are usually carried out under conventional conditions or under conditions recommended by the manufacturer.

[0053] The raw materials used in this application are all conventional products on the market.

[0054] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0055] Embodiment 1: The Bayer red mud raw material from Liaocheng, Shandong Province was used as the raw material for preparing the oxygen carrier, wherein the composition of the red mud raw material is shown in Table 1. Limestone (90% calcium carbonate) is a high calcium additive. The two were crushed, dried, ball-milled, and dried at 105°C for 12 hours to obtain fine powders with a particle size of 5-50 microns. 30 grams of red mud powder and 20 grams of limestone powder were taken respectively, and they were fully stirred and mixed to obtain 50 grams of red mud-based oxygen carrier precursors. The red mud-based oxygen carrier precursors were pressed and placed in a high-temperature crucible, and placed in a high-temperature muffle furnace at 1200°C for heat treatment for 5 hours. After the end, they were slowly cooled to room temperature in the furnace and taken out.

[0056] The heat-treated product in the crucible is a dark brown microcrystalline glass with a smooth surface. XRD results show that its main crystal components are 2CaO·Al2O3·SiO2 and CaTiO3, and the remaining components are amorphous phases formed after melting. After the product is peeled off from the crucible, red mud-based oxygen carrier particles with a particle size of 150 to 350 microns are obtained through crushing and screening.

[0057] Take 5 grams of the prepared red mud-based oxygen carrier and use a fluidized bed reactor to test its oxygen carrying capacity and fluidized abrasion resistance during the cyclic redox process. The reducing atmosphere is 5% methane, the oxidizing atmosphere is 20% oxygen, and the reaction time for each cycle is 20 minutes. The results are as follows Figure 3 As shown: after 30 cycles, the methane fuel conversion rate is 38.5%, the carbon dioxide selectivity is 70.1%, the oxygen carrying capacity of the oxygen carrier is good, the particle size of the red mud-based oxygen carrier particles remains almost unchanged during the cycle, and the fluidization strength is excellent.

[0058] Table 1 Composition of red mud raw materials

[0059] Embodiment 2: The Bayer red mud raw material of Example 1 was used as the raw material for preparing the oxygen carrier, and limestone was used as the high calcium additive. The two were crushed, dried, ball-milled, and dried at 105°C for 2h to obtain fine powders. 35g of red mud powder and 15g of limestone powder were taken respectively, and 50g of red mud-based oxygen carrier precursor was obtained by stirring and mixing. After pressing, the mixture was placed in a high-temperature crucible, and placed in a high-temperature muffle furnace at 1200°C for heat treatment for 5 hours. After the heat treatment, the mixture was slowly cooled to room temperature in the furnace and then taken out.

[0060] The heat-treated product in the crucible is a dark brown microcrystalline glass with a smooth surface. XRD results show that its main crystal components are 2CaO·Al2O3·SiO2 and CaTiO3, and the remaining components are amorphous phases formed after melting. After the product is peeled off from the crucible, oxygen carrier particles with a particle size of 150 microns to 350 microns are obtained through crushing and screening.

[0061] The fluidized bed reactor in Example 1 was used to test its oxygen carrying capacity and fluidization wear resistance. After 30 cycles, the methane fuel conversion rate was 39.3%, the carbon dioxide selectivity was 72.7%, the oxygen carrying capacity was good, the particle size of the red mud-based oxygen carrier particles remained almost unchanged during the cycle, and the fluidization strength was excellent.

[0062] Embodiment 3: The Bayer red mud raw material of Example 1 was used as the raw material for preparing the oxygen carrier, and limestone was used as an additive. The two were crushed, dried, ball-milled, and dried at 105°C for 2h to obtain fine powders. 40g of red mud powder and 10g of limestone powder were taken respectively, and 50g of red mud-based oxygen carrier precursor was obtained by stirring and mixing them uniformly. The mixture was placed in a high-temperature crucible and placed in a high-temperature muffle furnace at 1200°C for heat treatment for 5 hours. After the mixture was finished, the mixture was slowly cooled to room temperature in the furnace and then taken out.

[0063] The heat treatment product in the crucible is a partially molten brown irregular sintered body. XRD results show that its main mineral components are Fe2O3, Fe2TiO4, Na7Al7SiO 16 After the product is separated from the crucible, oxygen carrier particles with a particle size of 150 microns to 350 microns are obtained by crushing and screening.

[0064] The fluidized bed reactor of Example 1 was used to test its oxygen carrying capacity and fluidization wear resistance. After 30 cycles, the methane fuel conversion rate was 40.6%, the carbon dioxide selectivity was 75.9%, the oxygen carrying capacity was good, the average particle size of the red mud-based oxygen carrier particles decreased by about 5% during the cycle, and the fluidization strength was good.

[0065] Embodiment 4: The limestone in Example 1 was replaced by steel slag, and the remaining steps were the same, wherein the composition of the steel slag was as shown in Table 2.

[0066] Table 2

[0067] The heat-treated product in the crucible was a dark brown microcrystalline glass with a smooth surface. After 30 cycles, the methane fuel conversion rate was 39.3%, the carbon dioxide selectivity was 76.5%, the oxygen carrying capacity was good, the particle size of the red mud-based oxygen carrier particles remained almost unchanged during the cycle, and the fluidization strength was excellent.

[0068] Embodiment 5: The limestone in Example 2 is replaced by the steel slag in Example 4. The remaining steps are the same. The heat-treated product in the crucible is a dark brown microcrystalline glass with a smooth surface. After 30 cycles, the methane fuel conversion rate is 40.4%, the carbon dioxide selectivity is 77.1%, the oxygen carrying capacity is good, the particle size of the red mud-based oxygen carrier particles is almost unchanged during the cycle, and the fluidization strength is excellent.

[0069] Embodiment 6: The limestone in Example 3 is replaced by the steel slag in Example 4. The remaining steps are the same. The heat treatment product obtained in the crucible is a partially molten brown irregular sintered body. After 30 cycles, the methane fuel conversion rate is 41.6%, the carbon dioxide selectivity is 78.4%, the oxygen carrying capacity is good, the average particle size of the red mud-based oxygen carrier particles is reduced by about 10% during the cycle, and the fluidization strength is good.

[0070] Embodiment 7: In Example 1, limestone is replaced by slag, and the remaining steps are the same. The composition of the slag is shown in Table 3.

[0071] Table 3

[0072] The heat-treated product in the crucible was a dark brown microcrystalline glass with a smooth surface. After 30 cycles, the methane fuel conversion rate was 38.8%, the carbon dioxide selectivity was 70.7%, the oxygen carrying capacity was good, the particle size of the red mud-based oxygen carrier particles remained almost unchanged during the cycle, and the fluidization strength was excellent.

[0073] Embodiment 8: The limestone in Example 2 is replaced by the slag in Example 7. The remaining steps are the same. The heat-treated product obtained in the crucible is a partially molten dark brown irregular sintered body. After 30 cycles, the methane fuel conversion rate is 39.9%, the carbon dioxide selectivity is 72.6%, the oxygen carrying capacity is good, the particle size of the red mud-based oxygen carrier particles is almost unchanged during the cycle, and the fluidization strength is excellent.

[0074] Embodiment 9: The limestone in Example 3 is replaced by the slag in Example 7. The remaining steps are the same. The heat-treated product obtained in the crucible is a partially molten brown-black irregular sintered body. After 30 cycles, the methane fuel conversion rate is 40.4%, the carbon dioxide selectivity is 75.8%, the oxygen carrying capacity is good, the average particle size of the red mud-based oxygen carrier particles is reduced by about 10% during the cycle, and the fluidization strength is good.

[0075] Embodiment 10: In Example 1, limestone was replaced by sintered red mud. The remaining steps were the same. The composition of sintered red mud is shown in Table 4.

[0076] Table 4

[0077] The heat-treated product in the crucible was a dark brown microcrystalline glass with a smooth surface. After 30 cycles, the methane fuel conversion rate was 39.2%, the carbon dioxide selectivity was 76.1%, the oxygen carrying capacity was good, the particle size of the red mud-based oxygen carrier particles remained almost unchanged during the cycle, and the fluidization strength was excellent.

[0078] Embodiment 11: The limestone in Example 2 was replaced by the sintering red mud in Example 10. The remaining steps were the same. The heat-treated product in the crucible was a partially molten irregular dark brown sintered body. After 30 cycles, the methane fuel conversion rate was 40.1%, the carbon dioxide selectivity was 76.9%, the oxygen carrying capacity was good, the particle size of the red mud-based oxygen carrier particles remained almost unchanged during the cycle, and the fluidization strength was excellent.

[0079] Embodiment 12: The limestone in Example 3 is replaced by the sintered red mud in Example 10. The remaining steps are the same. The heat-treated product obtained in the crucible is a partially molten brown-black irregular sintered body. After 30 cycles, the methane fuel conversion rate is 41.4%, the carbon dioxide selectivity is 78.1%, the oxygen carrying capacity is good, the average particle size of the red mud-based oxygen carrier particles is reduced by about 10% during the cycle, and the fluidization strength is good.

[0080] Comparative Example 1: The Bayer red mud in Example 1 was used as the raw material for preparing the oxygen carrier. It was crushed, dried, ball-milled, and dried at 105°C for 2h to obtain fine powder. 50g of the red mud powder was placed in a high-temperature crucible and placed in a high-temperature muffle furnace at 1200°C for heat treatment for 5 hours. After the heat treatment, it was slowly cooled to room temperature in the furnace and then taken out.

[0081] The heat-treated product in the crucible is a brown-red regular sintered body. XRD results show that its main mineral components are Fe2O3, Na7Al7SiO 16 , nepheline KNa3[AlSiO4]4. After the product is separated from the crucible, the oxygen carrier particles with a particle size of 150 microns to 350 microns are obtained by crushing and screening.

[0082] The fluidized bed reactor of Example 1 was used to test its oxygen carrying capacity and fluidization wear resistance. After 30 cycles, the methane fuel conversion rate was 43.8%, the carbon dioxide selectivity was 80.4%, and the oxygen carrying capacity was excellent. During the cycle, the average particle size of the red mud-based oxygen carrier particles decreased by about 40%, and the fluidization strength was poor.

[0083] Comparative Example 2: Take the Bayer red mud of Example 1 as the raw material for preparing the oxygen carrier, and limestone as the additive. Both are crushed, dried, ball-milled, and dried at 105°C for 2h to obtain fine powders, and 45g of red mud powder and 5g of limestone powder are taken respectively, and 50g of red mud-based oxygen carrier precursor is obtained by stirring and mixing, which is placed in a high-temperature crucible, and placed in a high-temperature muffle furnace at 1200°C for heat treatment for 5 hours. After the end, the mixture is slowly cooled to room temperature in the furnace and taken out.

[0084] The heat-treated product in the crucible is a brown irregular sintered body. XRD results show that its main mineral components are Fe2O3, Fe2TiO4, Na7Al7SiO 16 . After the product is separated from the crucible, oxygen carrier particles with a particle size of 150 microns to 350 microns are obtained by crushing and screening. The oxygen carrying capacity and fluidization wear resistance of the fluidized bed of Example 1 are tested by thermogravimetric method. After 30 cycles, the fuel conversion rate is 41.8%, the carbon dioxide selectivity is 77.7%, and the oxygen carrying capacity is good. During the cycle, the average particle size of the red mud-based oxygen carrier particles decreases by about 15%, and the fluidization strength is poor.

[0085] Comparative Example 3: In Example 1, the muffle furnace heat treatment temperature is 1100 degrees Celsius, and the other steps are the same. The heat-treated product in the crucible is a brown-black sintered body, which is soft and brittle and does not have fluidization wear resistance.

[0086] Comparative Example 4: In Example 2, the muffle furnace heat treatment temperature is 1100 degrees Celsius, and the remaining steps are the same. The heat-treated product in the crucible is a brown sintered body, which is soft and brittle and does not have fluidized wear resistance.

[0087] Comparative Example 5: In Example 3, the muffle furnace heat treatment temperature is 1100 degrees Celsius, and the other steps are the same. The heat-treated product obtained in the crucible is a brown-red sintered body, which is soft and brittle and does not have fluidized wear resistance.

[0088] Comparative Example 6: In Comparative Example 1, the muffle furnace heat treatment temperature is 1100 degrees Celsius, and the remaining steps are the same. The heat-treated product in the crucible is a dark brown sintered body, which is soft and brittle and does not have fluidization wear resistance.

[0089] Comparative Example 7: In Comparative Example 2, the muffle furnace heat treatment temperature is 1100 degrees Celsius, and the remaining steps are the same. The heat-treated product obtained in the crucible is a brown-red sintered body, which is soft and brittle and does not have fluidization wear resistance.

[0090] Comparative Example 8: In Comparative Example 2, limestone was replaced by steel slag. The remaining steps were the same. The heat-treated product obtained in the crucible was a brown irregular sintered body. After 30 cycles, the methane fuel conversion rate was 42.9%, the carbon dioxide selectivity was 79.7%, the oxygen carrying capacity was good, the average particle size of the red mud-based oxygen carrier particles decreased by about 20% during the cycle, and the fluidization strength was poor.

[0091] Comparative Example 9: In Comparative Example 2, limestone was replaced with slag. The remaining steps were the same. The heat-treated product obtained in the crucible was a brownish-red cylindrical sintered body. After 30 cycles, the methane fuel conversion rate was 41.5%, the carbon dioxide selectivity was 77.6%, the oxygen carrying capacity was good, the average particle size of the red mud-based oxygen carrier particles decreased by about 30% during the cycle, and the fluidization strength was poor.

[0092] Comparative Example 10: In Comparative Example 2, limestone was replaced by sintered red mud. The remaining steps were the same. The heat-treated product in the crucible was a brownish-red cylindrical sintered body. After 30 cycles, the methane fuel conversion rate was 42.7%, the carbon dioxide selectivity was 79.4%, the oxygen carrying capacity was good, the average particle size of the red mud-based oxygen carrier particles decreased by about 30% during the cycle, and the fluidization strength was poor.

[0093] Comparative Example 11: In Example 1, limestone is replaced by coal gangue. The remaining steps are the same. The composition of coal gangue is shown in Table 5 below.

[0094] Table 5

[0095] The heat-treated product in the crucible is a brown-red sintered body, which is soft and brittle and does not have fluidization wear resistance.

[0096] Comparative Example 12: The limestone in Example 2 is replaced by the coal gangue in Comparative Example 11. The remaining steps are the same. The heat-treated product in the crucible is a brown-red sintered body, which is soft and brittle and does not have fluidization wear resistance.

[0097] Comparative Example 13: The limestone in Example 3 was replaced by the coal gangue in Comparative Example 11. The remaining steps were the same. The heat-treated product in the crucible was a brown-red sintered body, which was soft and brittle and did not have fluidized wear resistance.

[0098] Comparative Example 14: The limestone in Comparative Example 2 was replaced by the coal gangue in Comparative Example 11. The remaining steps were the same. The heat-treated product in the crucible was a brown-red sintered body, which was soft and brittle and did not have fluidized wear resistance.

[0099] Conclusion: The red mud-based oxygen carrier prepared in this application has the advantages of low cost, waste recycling, high fluidization wear resistance, reasonable preparation energy consumption, and standard cyclic oxygen carrying capacity. These advantages make this application have a wide industrial application market in the application scenarios of fluidized chemical chain combustion.

[0100] Through preparation methods such as calcium additives and heat treatment, red mud-based oxygen carrier particles that meet the particle size requirements of chemical looping combustion and fluidization wear strength are obtained. They have an operating life of more than 30 cycles and more than 12 hours of fluidization without wear, meeting the requirements for the oxygen carrying capacity of oxygen carriers in chemical looping combustion.

[0101] Through this application, a red mud-based high-strength chemical looping combustion oxygen carrier can be obtained. This application is that it can reduce the cost of preparing raw materials, recycle industrial solid wastes such as red mud, enhance the wear resistance of the oxygen carrier during the fluidization process, reduce the energy consumption of the preparation process, and meet the demand for the cyclic oxygen carrying capacity of the oxygen carrier in chemical looping combustion. The preparation process of the red mud-based oxygen carrier can realize large-scale industrial production.

[0102] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A red mud-based oxygen carrier, characterized in that: The raw materials of the red mud-based oxygen carrier include red mud powder and high calcium additive powder, wherein the weight ratio of the red mud powder to the high calcium additive powder is (3-4): (1-2).

2. The red mud-based oxygen carrier according to claim 1, characterized in that: The red mud powder and the high calcium additive powder are obtained by pre-treating the red mud raw material and the high calcium additive; the pre-treatment comprises: drying, crushing, drying and ball milling the red mud raw material and the high calcium additive to obtain the red mud powder and the high calcium additive powder; and / or, The particle sizes of the red mud powder and the high calcium additive powder are 5-50 microns.

3. The red mud-based oxygen carrier according to claim 2, characterized in that The red mud raw material has a ferric oxide content of more than 40% by mass; a sum of silicon dioxide and aluminum oxide content of more than 30% by mass; and / or The high calcium additive is at least one of limestone, sintering red mud, high calcium steel slag, and high calcium slag; and / or The calcium oxide content in the high calcium additive is greater than 40% by mass.

4. A method for preparing a red mud-based oxygen carrier according to any one of claims 1 to 3, characterized in that: include: 1) Pretreatment of raw materials, including: drying, crushing, drying, and ball milling the red mud raw materials and high calcium additives to obtain red mud powder and high calcium additive powder; 2) Preparation of a red mud-based oxygen carrier precursor, comprising: mixing the red mud powder with the high calcium additive powder to form a red mud-based oxygen carrier precursor; 3) Granulation and high-temperature heat treatment, including: pressing and molding the red mud-based oxygen carrier precursor to obtain a brick-shaped body; calcining the brick-shaped body at a high temperature to obtain a red mud-based oxygen carrier sintered brick; and 4) Processing and obtaining the finished red mud-based oxygen carrier product, including: cooling, crushing and screening the red mud-based oxygen carrier sintered bricks to obtain the finished red mud-based oxygen carrier product.

5. The method according to claim 4, characterized in that In step 1), the drying includes drying in an oven at a temperature of 100-120° C.; the drying time is 10-14 hours; Optionally, the drying temperature is 105° C.; the drying time is 12 h.

6. The method according to claim 4 or 5, characterized in that In step 2), in the red mud-based oxygen carrier precursor, the sum of the mass fractions of calcium oxide and magnesium oxide is equal to the sum of the mass fractions of silicon dioxide and aluminum oxide; and / or The red mud-based oxygen carrier precursor has a ferric oxide content of more than 25% by mass; and / or The mixing includes: mechanically mixing the red mud powder and the high calcium additive powder, or mixing the red mud powder and the high calcium additive powder in the form of slurry.

7. The method according to claim 4 or 5, characterized in that: The temperature of the high temperature calcination is 1200-1400°C, and the time of the high temperature calcination is 3-10h; Optionally, the high temperature calcination temperature is 1200° C. and the time is 5 hours.

8. The red mud-based oxygen carrier according to claim 4 or 5, characterized in that: In step 4), the red mud-based oxygen carrier is a particle with a particle size of 150 to 350 microns.

9. A red mud-based oxygen carrier prepared by the method according to any one of claims 4 to 8.

10. Use of the red mud-based oxygen carrier according to any one of claims 1 to 3 or the red mud-based oxygen carrier according to claim 9 in a chemical looping combustion / gasification process.

Citation Information

Patent Citations

  • Preparation method of modified red mud oxygen carrier for methane chemical chain steam reforming

    CN115072658A